Community syndicalism for the United States: preliminary observations on law and globalization in democratic production - Kenneth M. Casebeer (Oñati Socio-Legal Series)
The Great Recession resulting from the globalization of Finance Capitalism created two structural labor crises for developed economies: 1) The channeling of substantial investment into non-productive, paper commodities, reducing growth of production for use and therefore reducing available aggregate job creation; and 2) The continued exportation of industrial jobs to other lower cost jurisdictions, and outsourcing, automation, just-in-time production, and speed-ups associated with global supply chains. As a result, local communities and regional populations have destabilized and even collapsed with attendant social problems. One possible response is Community Syndicalism – local community finance and operating credit for industrial production combined with democratic worker ownership and control of production. The result would increase investment directly for production, retain jobs in existing population centers, promote job skilling, and retain tax bases for local services and income supporting local businesses, at the same time increasing support for authentic political democracy by rendering the exploitive ideology of the Public/Private distinction superfluous. Slowing job exportation may reduce the global race to the bottom of labor standards and differential wage rates reducing the return to producers of value and increasing the skew of income distribution undermining social wages and welfare worldwide. Community Syndicalism can serve as moral goal in an alternative production model focusing incentives on long term stability of jobs and community economic base.